Effect of Diethyl Ether on Performance and Exhaust Gas Emissions of Heavy-Duty Diesel Engines Fueled with Biodiesel-Diesel Blend (B35) - Hardiyanto, Catur; Prawoto, Prawoto (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2023)
To accelerate the energy transition, starting February 1, 2023, the Indonesian government has made it mandatory to use biodiesel (B35). Biodiesel has different characteristics from diesel oil, especially its greater viscosity and density, lower heating value, and high NOx emission. Therefore, this research has been carried out by adding the additive diethyl ether (DEE) to B35 to reduce the viscosity and density, increase the cetane number, and reduce emissions. The effects of diethyl ether on engine performances have been evaluated, including parameters of torque, power, brake thermal efficiency, brake-specific fuel consumption, exhaust emissions, and lubricants. The fuels used are B35 (35% FAME palm oil + 65% diesel oil), and B35 + DEE, with a DEE volume percentage of 3% to 6%. Diesel fuel (B0) was used as a comparison. Tests were carried out in the engine performance test laboratory using the heavy-duty diesel engine Komatsu SAA12V140E-3 at various engine speeds. The test results showed that adding diethyl ether slightly increases the average maximum power, increases brake thermal efficiency, and reduces brake-specific fuel consumption and emissions compared to B35. Very significant effects were seen in NOx and SO2 exhaust emissions. At maximum load, the mixture with 4% diethyl ether gave the greatest brake thermal efficiency, the lowest brake-specific fuel consumption, and the greatest reduction in NOx and SO2 emissions, respectively 7.69%, 6.30%, 53.48%, and 40.89% compared to B35, and 2.24%, (-0.90%), 48.88% and 71.17% compared to B0, respectively. Evaluation of lubricating oil during the performance test did not show a significant difference for all types of fuel used.